2006
DOI: 10.1080/10242420500518482
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of chitinases A, B and C fromSerratia marcescens

Abstract: Serratia marcescens produces three chitinases, ChiA, ChiB and ChiC which together enable the bacterium to efficiently degrade the insoluble chitin polymer. We present an overview of the structural properties of these enzymes, as well as an analysis of their activities towards artificial chromogenic chito-oligosaccharide-based substrates, chito-oligosaccharides, chitin and chitosan. We also present comparative inhibition data for the pseudotrisaccharide allosamidin (an analogue of the reaction intermediate) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 45 publications
1
79
0
Order By: Relevance
“…Thus, some degree of substrate affinity may be expected in additional aglycon subsites, and this has indeed been observed [25]. Previous studies of ChiB catalyzed hydrolysis of CHOS have shown that (GlcNAc) 3 productively binds from À2 to +1, (GlcNAc) 4 productively binds from À2 to +2, and that (GlcNAc) 5 productively binds from À2 to +3 [25]. The preferential binding of (GlcNAc) 5 to subsites À2 to +3 was confirmed by the crystal structure of this ligand in complex with ChiB-E144Q [26].…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Thus, some degree of substrate affinity may be expected in additional aglycon subsites, and this has indeed been observed [25]. Previous studies of ChiB catalyzed hydrolysis of CHOS have shown that (GlcNAc) 3 productively binds from À2 to +1, (GlcNAc) 4 productively binds from À2 to +2, and that (GlcNAc) 5 productively binds from À2 to +3 [25]. The preferential binding of (GlcNAc) 5 to subsites À2 to +3 was confirmed by the crystal structure of this ligand in complex with ChiB-E144Q [26].…”
Section: Resultsmentioning
confidence: 68%
“…The preferential binding of (GlcNAc) 5 to subsites À2 to +3 was confirmed by the crystal structure of this ligand in complex with ChiB-E144Q [26]. (GlcNAc) 6 productively binds from À3 to +3 (approximately 20 %) and from À2 to ''+4" (80%; ''+4" denotes a binding position next to the +3 subsite) [25]. Combining this information with the obtained thermodynamic parameters (Table 1) allows for the estimation of binding energies for individual subsites.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…FTD-0668), and was found to be a potent inhibitor of blowfly 6 and Serratia marcescens chitinases (SmChi). [9][10][11][12] Recently, argifin complexes with fungal (Aspergillus fumigatus), human and bacterial chitinases have been resolved by X-ray crystallography. 11,12 These studies revealed that there are at least four conserved hydrogenbond interactions between the N o -methylcarbamoyl-L-arginine moiety and the polar groups arrayed in the hydrolytic pocket of the family 18 chitinases examined to date.…”
Section: Introductionmentioning
confidence: 99%
“…FO-7314 and Gliocladium sp. FTD-0668, respectively, by our research group, and found to be potent chitinase inhibitors of blowfly (Lucilia cuprina) 10 and Serratia marcescens chitinases (SmChi), [13][14][15][16] both of which are family-18 chitinases (Figure 1). Developments of practical and efficient total syntheses of 1 and 2 are important objectives, as the original sources do not produce these cyclic peptides with sufficient quantities.…”
Section: Introductionmentioning
confidence: 99%